Active suspension control of three axle railway vehicle - Mohammad Saberi, Ahmad (2009)
Nowadays, active suspension system is commonly used in many vehicles to overcome the limitation of passive suspension. This project will apply the active suspension system into the railway vehicles to study the performance of the train. This paper will focus for three axle railway vehicle. In term to study the three axle railway vehicle, there are four results that need to be observed. The four results that should be observed are control torque, lateral displacement, yaw angle, and body acceleration. We will use different value of parameter to see the parameter’s characteristic that will contribute to better performance. The parameters that will be tested are cant angle, curving track radius and vehicle velocity. The system will be form in state space equation. From state space equation, three axle railway vehicles will be presented using MATLAB application. Linear quadratic regulator is used to be the controller in this project. Simulation on MATLAB application is analyzed.